(untitled) (مجلة إحالات, 2026)
The current research paper attempts to investigate the research problem that occupies an important central position in the preparation of any academic scientific research, and on which its success depends, so that it is fundamentally linked to the subject, and its impact is evident in all the steps that follow, as it determines the type of study and the nature of the approach that is followed. And the study plan and its tools, and based on this vision, this paper came to answer the following problem: What is meant by the research problem? And what is its importance in creating research knowledge?, concluding that creating solid scientific outputs depends on the extent of controlling the steps of scientific research.